Diagnosis, treatment and prevention of infective endocarditis: Turkish consensus report-2019 - (:unkn) unknown (AVES, 2020)
Infective endocarditis (IE) is a rare but still important as an infectious disease due to high rate of morbidity and substantial mortality. Although IE is not a notifiable disease in Turkey, and an incidence study has not been performed, the incidence may be higher than that in the developed countries due to frequent predisposing cardiac conditions and higher rates of nosocomial bacteremia, which may lead to IE in risk groups. IE generally affects the elderly in developed countries but it is frequently encountered among young individuals in Turkey. In order to reduce mortality and morbidity, it is critical to diagnose IE, to determine the causative agent, and to start treatment rapidly. Most patients cannot be diagnosed at the first visit, about half can be diagnosed after 3 months, and the disease often goes unnoticed. In patients diagnosed with IE, the rate of the identification of a causative organism is significantly lower in Turkey than that in developed countries. Some important microbiological diagnostic tests are not performed in most centers and several antimicrobials that are recommended as the first option for the treatment particularly antistaphylococcal penicillins, are unavailable in Turkey. These problems necessitate reviewing the epidemiological, laboratory, and clinical characteristics of IE in our country, as well as the current information about its diagnosis, treatment, and prevention together with local data. The diagnosis and treatment processes of IE should be standardized at every stage so that the management can be conducted in a setting in which physicians of various specialties are involved and is consistent with the current recommendations. The Study Group for Infective Endocarditis and Other Cardiovascular Infections of the Turkish Society of Clinical Microbiology and Infectious Diseases called for the collaboration of the relevant specialist organizations to establish a consensus report on the diagnosis, treatment, and prevention of IE in the context of current information and local data in Turkey.
Keywords: Consensus report; infective endocarditis; RESISTANT STAPHYLOCOCCUS-AUREUS; BLOOD-STREAM INFECTIONS; HIGH-DOSE DAPTOMYCIN; MINIMUM INHIBITORY CONCENTRATION; PROSTHETIC VALVE ENDOCARDITIS; CIRCULATING IMMUNE-COMPLEXES; NONBACTERIAL THROMBOTIC ENDOCARDITIS; CULTURE-NEGATIVE ENDOCARDITIS; AMPICILLIN PLUS CEFTRIAXONE; IN-HOSPITAL MORTALITY